Analysis of Public Policy Evaluation at The Environmental Service of Serang City in Waste Management - Dede Qodrat Alwajir; Parko Prahima; Arief Rachman; Try Adhi Try Adhi Bangsawan (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The author conducted this research to determine the evaluation analysis of public policy at the Serang City Environmental Service in waste management. The aim is whether the waste handling carried out by the environmental service is going well or vice versa, with an evaluation we can find out what obstacles occur in waste management. This research was carried out in the Banten area, specifically in the city of Serang. This research method was carried out through literature studies and journal reviews, especially those that can be accessed online. Researchers view that a qualitative approach will help researchers in collecting data. This research method uses a qualitative descriptive method, where analyzing the data is described in descriptive form. According to qualitative descriptive research, it is research that attempts to describe an event in the research object being analyzed so as to produce a solution to a problem. The implementation of waste management carried out by the Serang City government has not yet been fully implemented as stated in Regional Regulation Number 7 of 2021 concerning Waste Management. Based on the results of this analysis, it can be said that policy evaluation in Serang City has not been optimal because waste management is still the main issue. that needs to be resolved by the government. One of them is an unorganized rubbish dump. And community participation is still low. This issue has led to environmental pollution, thus creating discomfort for the community